Gabriel Naudé, Helluo Librorum, e l'Advis pour dresser une bibliothèque - Serrai, Alfredo (Biblioteche & bibliotecari / Libraries & librarians, 2021)
Alfredo Serrai in the volume Gabriel Naudé, Helluo Librorum, e l'Advis pour dresser une bibliothèque, publish the version from French to Italian of the first exposition of the Librarianship as a discipline, together with an ample introduction both historical and conceptual. With the arguments and the praxis introduced and explained by Naudé, in the first decades of the XVII century has begun the discipline "Librarianship as the science of the selection and of the order of books" that implement their disposition in a library. With Naudé the library becomes not only the proper image of the science, but a true testimonial of the verity against its manipulations and errors. In such a vision of both the research and morality, the naudean philosophical principles can be properly situated in the frame of a mature preilluminism.